Polyvinyl acetal resin
Through 13C-NMR measurement and viscosity optimization, the problems of insufficient corrosion resistance and tensile strength of ceramic green sheets are solved, and the reliability and productivity of stacked ceramic capacitors are improved.
Patent Information
- Application Number
- CN202380040610.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-24
- Filing Date
- 2023-12-05
- Publication Date
- 2024-12-27
AI Technical Summary
When the existing polyvinyl acetal resin is used to produce ceramic green sheets, the sheet corrosion resistance and tensile strength are insufficient, resulting in a decrease in electrical characteristics of the laminated ceramic capacitors and a deterioration rate.
The peak integral ratio and weight average molecular weight of the submethyl C atoms in the triple unit of the polyvinyl acetal resin were optimized by 13C-NMR measurement, and combined with appropriate viscosity and hydroxyl amount distribution, it was prepared with excellent sheet resistance with the following materials. Resin with corrosion and tensile strength.
The high corrosion resistance and tensile strength of ceramic green sheets are achieved, the reliability and productivity of stacked ceramic capacitors are improved, and the reduction of electrical characteristics and disadvantages are reduced.
Smart Images

Figure CN119213039A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to polyvinyl acetal resin. Background Art
[0002] In recent years, electronic components mounted in various electronic devices have been miniaturized and laminated, and laminated electronic components such as multilayer circuit boards, laminated coils, and laminated ceramic capacitors have been widely used.
[0003] Among them, multilayer ceramic capacitors are generally manufactured through the following steps.
[0004] First, after adding a plasticizer, a dispersant, etc. to a solution obtained by dissolving a binder resin such as a polyvinyl butyral resin or a poly (meth) acrylate resin in an organic solvent, a ceramic raw material powder is added, and the mixture is uniformly mixed by a mixing device such as a bead mill or a ball mill, and a slurry composition having a certain viscosity is obtained after degassing. The slurry composition is cast onto a support surface such as a polyethylene terephthalate film or a SUS plate after demolding using a scraper or a reverse roll coater, and the volatile components such as a solvent are distilled off by heating, and then the ceramic green sheet is obtained by peeling off from the support.
[0005] Next, a conductive paste to be the internal electrode is applied to the obtained ceramic green sheet by screen printing, and a plurality of sheets of the obtained material are alternately stacked and heat-pressed to produce a laminate. Then, a process of removing the binder resin component contained in the laminate by thermal decomposition, i.e., a so-called degreasing process, is performed, and the end surface of the ceramic sintered body obtained by firing is sintered to the external electrode to obtain a laminated ceramic capacitor.
[0006] However, conventional polyvinyl acetal resins produce a small amount of undissolved matter when dissolved in an organic solvent. If such undissolved matter exists, voids are likely to remain in the degreasing process and the firing process when manufacturing a laminated ceramic capacitor, or the dispersibility of the ceramic powder is reduced. As a result, the electrical properties of the obtained product are reduced.
[0007] Therefore, when the polyvinyl acetal resin is used for ceramic green sheets, it is necessary to mix it with an organic / inorganic compound or the like, dissolve it in an organic solvent, and then perform a filtration step to remove undissolved matter.
[0008] In this regard, Patent Document 1 proposes a polyvinyl acetal resin. When filtering a polyvinyl acetal resin solution prepared by dissolving the resin in a 1:1 mixed solvent of methyl ethyl ketone and / or toluene and ethanol to form a 5 wt% solution at a filtration temperature of 25°C and a filtration pressure of 10 mmHg using a filter with a mesh size of 5 μm, the reduction rate of the filtration flow rate is less than 10%. In addition, Patent Document 2 proposes a polyvinyl acetal resin that controls the wave number A (cm -1 ) of the peak in the range of wave numbers 3100 - 3700 cm -1 in the IR absorption spectrum and the hydroxyl group content (mol%) within a specific range.
[0009] By using such a polyvinyl acetal resin, there are few undissolved substances when dissolved in an organic solvent, the filtration time can be shortened, and thus the productivity can be improved.
[0010] Prior Art Documents
[0011] Patent Documents
[0012] Patent Document 1: Japanese Patent Application Laid-Open No. 2005 - 325342
[0013] Patent Document 2: International Publication No. 2021 / 060499 Summary of the Invention
[0014] Problems to be Solved by the Invention
[0015] However, when using the polyvinyl acetal resin described in Patent Document 1, there is a problem that the sheet corrosion resistance (Japanese: 耐シートアタック性) and tensile strength of the obtained ceramic green sheet become insufficient. In addition, when using the polyvinyl acetal resin described in Patent Document 2, there is still room for improvement in the sheet corrosion resistance of the obtained ceramic green sheet. It should be noted that as the ceramic green sheet becomes thinner, if the sheet corrosion resistance and tensile strength are insufficient, sheet defects may sometimes occur, which become the main reasons for the deterioration of the electrical characteristics and the increase in the defect rate of the multilayer ceramic capacitor.
[0016] An object of the present invention is to provide a polyvinyl acetal resin that can obtain a ceramic green sheet with excellent sheet corrosion resistance and tensile strength, especially when used as a binder for a ceramic green sheet. As a result, it is possible to fabricate a multilayer ceramic capacitor with excellent reliability, in which the deterioration of the electrical characteristics and the increase in the defect rate of the multilayer ceramic capacitor are less likely to occur.
[0017] Means for Solving the Problems
[0018] The present invention (1) relates to a polyvinyl acetal resin, which is obtained by 13The ratio of the peak integral value of the secondary methyl C atom represented by (a)' in the triple unit represented by the following formula (a) obtained by C-NMR (nuclear magnetic resonance) measurement to the total peak integral value of the secondary methyl C atom represented by (a)', (b)', and (c)' in the triple unit represented by the following formula (a), the following formula (b), and the following formula (c) is greater than 0.22, and the weight average molecular weight of the above-mentioned polyvinyl acetal resin is greater than 230,000.
[0019] [Chemical formula 1]
[0020]
[0021] In the formula (b) and the formula (c), R is each independently hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
[0022] The present invention (2) relates to the polyvinyl acetal resin described in the present invention (1), wherein the polyvinyl acetal resin is 13 The ratio of the peak integral value of the methine C atom represented by (a)' in the triple unit represented by the formula (a) obtained by C-NMR (nuclear magnetic resonance) measurement to the total peak integral values of the methine C atoms represented by (a)', (b)' and (c)' in the triple units represented by the above formulas (a), (b) and (c) is greater than 0.23.
[0023] The present invention (3) relates to the polyvinyl acetal resin described in the present invention (1) or (2), wherein the solution viscosity is greater than 30 mPa·s and less than 600 mPa·s when a 5 mass % solution obtained by dissolving the polyvinyl acetal resin in a 1:1 mixed solvent of ethanol and toluene is measured using a B-type viscometer at a solution temperature of 20°C.
[0024] The present invention (4) relates to the polyvinyl acetal resin according to any one of the present inventions (1) to (3), wherein the amount of hydroxyl groups is 23 mol% or more and 40 mol% or less.
[0025] The present invention (5) relates to the polyvinyl acetal resin according to any one of the present inventions (1) to (4), wherein the amount of acetyl groups is 0.1 mol% or more and 5 mol% or less.
[0026] The present invention (6) relates to the polyvinyl acetal resin according to any one of the present inventions (1) to (5), wherein the molecular weight distribution of the polyvinyl acetal resin is 2.75 or less.
[0027] The present invention (7) relates to the polyvinyl acetal resin according to any one of the present inventions (1) to (6), which is used for a ceramic green sheet.
[0028] The present invention (8) relates to a slurry composition for ceramic green sheets, comprising the polyvinyl acetal resin according to any one of the present inventions (1) to (7), an organic solvent, and a ceramic powder.
[0029] The present invention (9) relates to a ceramic green sheet obtained by using the slurry composition for ceramic green sheets described in the present invention (8).
[0030] The present invention (10) relates to a multilayer ceramic capacitor obtained by using the ceramic green sheet described in the present invention (9).
[0031] Hereinafter, the present invention will be described in detail.
[0032] The present inventors have conducted intensive research and found that a ceramic green sheet obtained by using a polyvinyl acetal resin having excellent sheet corrosion resistance and tensile strength is excellent. 13 The present invention is completed by satisfying a specific relationship between the ratio of the peak integral value of the methine C atom represented by (a)' in the triple unit represented by the above formula (a) obtained by C-NMR measurement to the total peak integral values of the methine C atoms represented by (a)', (b)', and (c)' in the triple units represented by the above formulas (a), (b), and (c) (the ratio of the peak integral values of the triple unit formed by three sequences (Japanese: 3 chain) of structural units having hydroxyl groups) and the weight-average molecular weight.
[0033] Furthermore, when the polyvinyl acetal resin of the present invention is used as a slurry composition for ceramic green sheets, it is also possible to obtain an effect of preventing the viscosity of the slurry from increasing over time, thereby improving productivity.
[0034] For the polyvinyl acetal resin of the present invention, 13 The ratio of the peak integral value of the triplet unit formed by the three sequences of the structural unit having a hydroxyl group obtained by C-NMR measurement is 0.22 or more. By setting it to the above range, the corrosion resistance of the sheet can be improved. In addition, the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural unit having a hydroxyl group is preferably 0.23 or more.
[0035] The more preferred lower limit of the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups is 0.24, the further preferred lower limit is 0.25, the preferred upper limit is 0.32, and the more preferred upper limit is 0.30. That is, the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups is preferably 0.23 to 0.32, more preferably 0.24 to 0.32, and further preferably 0.25 to 0.30. If it is above the above lower limit, the hydrogen bonding property brought by the hydroxyl group is improved, and the ceramic green sheet produced using the polyvinyl acetal resin of the present invention can reduce the solubility in organic solvents, so that the corrosion resistance of the sheet becomes good. If it is below the above upper limit, the solubility of the polyvinyl acetal resin in organic solvents will not be excessively reduced, and the handling property of solution production, etc. becomes good.
[0036] It should be noted that in the present invention, the ratio of the peak integral value of "a triplet unit formed by three sequences of structural units having a hydroxyl group" is specified, thereby making it possible to more accurately confirm the continuity of the hydroxyl group compared to the case where the measurement is based on a binary unit formed by two sequences (Japanese: 2 chain).
[0037] The ratio of the peak integral values of the triplet unit formed by the three sequences of the structural units having hydroxyl groups is the ratio of the sum of the peak integral values of the methine C atoms represented by (a)' in the triplet unit represented by the above formula (a) to the sum of the peak integral values of the methine C atoms represented by (a)', (b)', and (c)' in the triplet units represented by the above formula (a), the above formula (b), and the above formula (c). 13 The measurement was performed by C-NMR.
[0038] The sum of the peak integral values of the methine C atoms represented by (a)', (b)', and (c)' in the triplet units represented by the above formula (a), the above formula (b), and the above formula (c) [I(a)'+I(b)'+I(c)'], when the peak integral values of the methine C atoms represented by (a)', (b)', and (c)' are calculated by 13 C-NMR (nuclear magnetic resonance) measurement 13 The integrated value of the peak attributable to the methine C atom at the position (f)' of the triple unit represented by the following formula (f) in the C-NMR spectrum is denoted as I(f)', the integrated value of the peak attributable to the methine C atom at the position (g)' of the triple unit represented by the following formula (g) is denoted as I(g)', and the integrated value of the peak attributable to the methine C atom at the position (k)' of the triple unit represented by the following formula (k) is denoted as I(g)'. 2 The integral value of the peak to which the methine C atom at the position belongs is set as I(k)' 2, when the integral value of the peak attributed to the secondary methyl C atom at the position (i)' of the triple unit shown by the following formula (i) is set to I(i)', the integral value of the peak attributed to the secondary methyl C atom at the position (j)' of the triple unit shown by the following formula (j) is set to I(j)', and the integral value of the peak attributed to the secondary methyl C atom at the position (m)' of the triple unit shown by the following formula (m) is set to I(m)', it can be calculated by their sum, that is, the following formula (4).
[0039] I(a)'+I(b)'+I(c)'=I(f)'+I(g)'+I(k)' 2 +I(i)'
[0040] +I(j)'+I(m)'(4)
[0041] [Chemical formula 2]
[0042]
[0043] R in formula (i), formula (j) and formula (m) 6 ~R 9 Each independently represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
[0044] Regarding the peak integral value [I(a)'] of the methine C atom represented by (a)' in the triple unit represented by the above formula (a), 13 C-NMR (nuclear magnetic resonance) measurement 13 The integrated value of the peak attributable to the methine C atom at the position (f)' of the triple unit represented by the above formula (f) in the C-NMR spectrum is denoted as I(f)', the integrated value of the peak attributable to the methine C atom at the position (g)' of the triple unit represented by the above formula (g) is denoted as I(g)', and the integrated value of the peak attributable to the methine C atom at the position (k)' of the triple unit represented by the above formula (k) is denoted as I(g)'. 2 The integral value of the peak to which the methine C atom at the position belongs is set as I(k)' 2 When , it can be calculated by summing them, that is, the following formula (5).
[0045] I(a)'=I(f)'+I(g)'+I(k)' 2 (5)
[0046] The ratio of the peak integral value of the secondary methyl C atom represented by (a)' in the triple unit represented by the above formula (a) to the total peak integral values of the secondary methyl C atoms represented by (a)', (b)', and (c)' in the triple units represented by the above formula (a), the above formula (b), and the above formula (c) [I(a)' / (I(a)'+I(b)'+I(c)')] can be calculated by the following formula (6).
[0047] I(a)' / (I(a)'+I(b)'+I(c)')=(I(f)'+I(g)'+I(k)' 2 ) / (I(f)'+I(g)'+I(k)' 2 +I(i)'+I(j)'+I(m)')(6)
[0048] exist 13 In the C-NMR spectrum, the above I(f)' is an integrated value of a peak in the range of 64.0 to 64.8 ppm, and the above I(g)' is an integrated value of a peak in the range of 65.8 to 66.7 ppm.
[0049] In addition, I(i)' is the peak integrated value in the range of 61.5 to 63.1 ppm, I(j)' is the peak integrated value in the range of 64.8 to 65.8 ppm, and I(m)' is the peak integrated value in the range of 63.1 to 64.0 ppm.
[0050] The above I(k)' 2 It is the integrated value based on the peak in the range of 66.7 to 70.5 ppm, but since it partially overlaps with the peaks of other structures, it can be calculated by the difference with other peaks. 2 For example, since the peak attributed to the methine C atom at the position (e1)' of the structural unit (e) described below also exists in the range of 66.7 to 70.5 ppm, the peak integral value can be calculated using the following formula (7).
[0051] Here, I(t) is the peak integral value in the range of 66.7 to 70.5 ppm, I(d1)' is the peak integral value in the range of 98.5 to 101.5 ppm to which the methine C atom of the acetal part having a meso-type 6-membered acetal ring at the position (d1)' of the structural unit (d) belongs, and I(e1)' is the peak integral value in the range of 91.5 to 101.5 ppm to which the methine C atom of the acetal part having a racemic 6-membered acetal ring at the position (e1)' of the structural unit (e) belongs. I(d2)' is the peak integration value in the range of 71.0 to 74.6 ppm to which the secondary methyl C atom of the main chain having a racemic 6-membered acetal ring at the position (d2)' of the structural unit (d) is attributed, and I(e2)' is the peak integration value in the range of 66.7 to 70.5 ppm to which the secondary methyl C atom of the main chain having a racemic 6-membered acetal ring at the position (e2)' of the structural unit (e) is attributed.
[0052] I(k) ' 2 =I(t)-I(d1) '×I(e2) '÷I(d2) ' (7)
[0053] [Chemical formula 3]
[0054]
[0055] R in formula (d) and formula (e) 4 , R 5 Each independently represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
[0056] The ratio of the peak integrated value of the triplet unit formed by three sequences of structural units having hydroxyl groups can be adjusted by, for example, appropriately setting the saponification degree of the raw material polyvinyl alcohol resin, the type of aldehyde, the conditions of the acetalization reaction, the acetal group content, the hydroxyl group content, and the acetyl group content of the polyvinyl acetal resin.
[0057] Specifically, the aging temperature (maintaining temperature) of the acetalization reaction is preferably 45° C. or higher, more preferably 50° C. or higher. By setting the reaction temperature to the above, the ratio of the peak integrated value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups can be increased, and the ratio of the peak integrated value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups specified in the present invention can be easily satisfied.
[0058] The polyvinyl acetal resin of the present invention preferably has a solution viscosity of 30 mPa·s to 600 mPa·s when a 5 mass % solution of the polyvinyl acetal resin dissolved in a 1:1 mixed solvent of ethanol and toluene is measured using a Brookfield viscometer at a solution temperature of 20°C.
[0059] From the viewpoint of being able to achieve good tensile strength, the above viscosity is 30 mPa·s or more, more preferably 50 mPa·s or more, and particularly preferably 60 mPa·s or more. From the viewpoint of being able to achieve good viscosity stability of the ceramic slurry composition, the above viscosity is 600 mPa·s or less, more preferably 400 mPa·s or less, and particularly preferably 200 mPa·s or less. That is, the above viscosity is preferably 30 to 600 mPa·s, more preferably 50 to 400 mPa·s, and particularly preferably 60 to 200 mPa·s.
[0060] As the B-type viscometer, for example, a TVB-10 viscometer manufactured by Toki Sangyo Co., Ltd. can be used. In addition, the rotor and rotation speed when measuring the viscosity are preferably appropriately adjusted according to the solution viscosity, and for example, it is preferred to use SPINDLE No. M1 to M4 for measurement within a rotation speed range of 0.3 to 100 rpm.
[0061] The above viscosity can be adjusted by appropriately setting the saponification degree of the raw material polyvinyl alcohol resin, the average degree of polymerization, the conditions of the acetalization reaction, the acetal group content, the hydroxyl group content, the acetyl group content, the weight average molecular weight, the number average molecular weight, the molecular weight distribution, etc. of the polyvinyl acetal resin.
[0062] Specifically, the aging temperature (maintenance temperature) in the acetalization reaction is preferably 45°C or higher, more preferably 50°C or higher, and preferably 75°C or lower, more preferably 72°C or lower. That is, the above-mentioned maintenance temperature is preferably 45 to 75°C, more preferably 50 to 72°C.
[0063] By setting it as the said retention temperature, the ratio of the peak integration value of the triplet unit formed by three sequences of the structural unit which has a hydroxyl group can be easily adjusted, and the viscosity prescribed|regulated in this invention can be easily satisfied.
[0064] The polyvinyl acetal resin of the present invention preferably has a structural unit having an acetal group represented by the following formula (1), a structural unit having a hydroxyl group represented by the following formula (2), and a structural unit having an acetyl group represented by the following formula (3).
[0065] [Chemical formula 4]
[0066]
[0067] In the above formula (1), R 1 It represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms.
[0068] In the above formula (1), R 1 In the case of an alkyl group having 1 to 20 carbon atoms, examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, 2-ethylhexyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, and octadecyl. Among them, methyl and n-propyl are preferred.
[0069] In the polyvinyl acetal resin of the present invention, the content of the structural unit having an acetal group represented by the above formula (1) (hereinafter also referred to as "acetal group amount") preferably has a lower limit of 55 mol% and an upper limit of 75 mol%.
[0070] When the acetal group content is 55 mol% or more, the solubility in an organic solvent can be improved, and when the acetal group content is 75 mol% or less, a polyvinyl acetal resin having excellent tensile strength can be obtained.
[0071] The more preferred lower limit of the acetal group content is 57 mol%, the further preferred lower limit is 60 mol%, and the more preferred upper limit is 73 mol%. That is, the acetal group content is preferably 55 to 75 mol%, more preferably 57 to 73 mol%, and further preferably 60 to 73 mol%.
[0072] The above acetal group amount can be 1 The measurement was performed by H-NMR.
[0073] In addition, regarding the method for calculating the amount of acetal groups, since the acetal groups of the polyvinyl acetal resin are obtained by acetalizing two hydroxyl groups of polyvinyl alcohol, a method of counting the two hydroxyl groups acetalized was adopted.
[0074] In the polyvinyl acetal resin of the present invention, the content of the structural unit having a hydroxyl group represented by the general formula (2) (hereinafter also referred to as "hydroxyl amount") preferably has a lower limit of 23 mol% and an upper limit of 40 mol%.
[0075] When the hydroxyl group content is 23 mol% or more, a polyvinyl acetal resin having high toughness can be obtained, and when the hydroxyl group content is 40 mol% or less, the solubility in an organic solvent can be sufficiently improved.
[0076] The more preferred lower limit of the amount of hydroxyl groups is 25 mol%, the further preferred lower limit is 27 mol%, the particularly preferred lower limit is 29 mol%, the more preferred upper limit is 35 mol%, and the further preferred upper limit is 33 mol%. That is, the amount of hydroxyl groups is preferably 23 to 40 mol%, more preferably 25 to 35 mol%, further preferably 27 to 33 mol%, and particularly preferably 29 to 33 mol%.
[0077] The above hydroxyl amount can be 1 The measurement was performed by H-NMR.
[0078] In the polyvinyl acetal resin of the present invention, the content of the structural unit having an acetyl group represented by the general formula (3) (hereinafter also referred to as "acetyl group amount") preferably has a lower limit of 0.1 mol % and an upper limit of 5 mol %.
[0079] If the acetyl group content is 0.1 mol% or more, the viscosity of the ceramic green sheet slurry composition can be suppressed due to hydrogen bonding within and between molecules of the hydroxyl groups in the polyvinyl acetal resin. If the acetyl group content is 5 mol% or less, the flexibility of the polyvinyl acetal resin will not be excessively increased, and the handling property can be improved.
[0080] The more preferred lower limit of the acetyl group amount is 0.3 mol%, the further preferred lower limit is 0.5 mol%, the more preferred upper limit is 4 mol%, the further preferred upper limit is 3 mol%, and the particularly preferred upper limit is 2 mol%. That is, the acetyl group amount is preferably 0.1 to 5 mol%, more preferably 0.3 to 4 mol%, further preferably 0.5 to 3 mol%, and particularly preferably 0.5 to 2 mol%.
[0081] The above acetyl group amount can be 1 The measurement was performed by H-NMR.
[0082] The lower limit of the weight average molecular weight (Mw) of the polyvinyl acetal resin of the present invention is 230000. When the weight average molecular weight is 230000 or more, the tensile strength can be made good.
[0083] The preferred lower limit of the weight average molecular weight is 270,000, and a more preferred lower limit is 290,000, and the preferred upper limit is 700,000, and a more preferred upper limit is 450,000. That is, the weight average molecular weight is preferably 270,000 to 700,000, and more preferably 290,000 to 450,000.
[0084] The number average molecular weight (Mn) of the polyvinyl acetal resin of the present invention preferably has a lower limit of 98,000, an upper limit of 250,000, and a more preferred upper limit of 160,000. That is, the number average molecular weight is preferably 98,000 to 250,000, and more preferably 98,000 to 160,000.
[0085] The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the polyvinyl acetal resin of the present invention, i.e., the molecular weight distribution, preferably has a lower limit of 2.2, a more preferred lower limit of 2.3, a preferred upper limit of 2.75, a more preferred upper limit of 2.73, and a further preferred upper limit of 2.7. That is, the Mw / Mn is preferably 2.2 to 2.75, more preferably 2.3 to 2.73, and further preferably 2.3 to 2.7.
[0086] The Mw and Mn can be measured, for example, by gel permeation chromatography (GPC) using an appropriate standard (for example, a polystyrene standard). Examples of the column used when measuring the Mw and Mn include TSKgel SuperHZM-H and the like.
[0087] For the polyvinyl acetal resin of the present invention, when a thin film ceramic green sheet is produced, from the viewpoint of maintaining mechanical strength, the lower limit of the average degree of polymerization is preferably 600, more preferably 800, and further preferably 1000. From the viewpoint of solubility in organic solvents and dissolution viscosity, the upper limit is preferably 4000, more preferably 3000, and further preferably 2500. That is, the average degree of polymerization is preferably 600 to 4000, more preferably 800 to 3000, and further preferably 1000 to 2500.
[0088] It should be noted that the average degree of polymerization of the polyvinyl acetal resin is the same as the average degree of polymerization of the raw material polyvinyl alcohol. The average degree of polymerization can be measured in accordance with JIS K6726.
[0089] The polyvinyl acetal resin of the present invention can be generally produced by acetalizing a polyvinyl alcohol resin.
[0090] As the polyvinyl alcohol resin, for example, a conventionally known polyvinyl alcohol resin such as a resin produced by saponifying a polyvinyl acetate-based resin with an alkali, an acid, ammonia water, or the like can be used.
[0091] The polyvinyl alcohol resin may be completely saponified, but if at least one unit having a dihydroxyl group (Japanese: 2-linked hydrocarbyl group) at the meso position and the racemic position is present at least in one part of the main chain, it does not need to be completely saponified and may be a partially saponified polyvinyl alcohol resin. In addition, as the polyvinyl alcohol resin, a copolymer of a monomer copolymerizable with vinyl alcohol such as an ethylene-vinyl alcohol copolymer resin and a partially saponified ethylene-vinyl alcohol copolymer resin and vinyl alcohol may also be used.
[0092] Examples of the polyvinyl acetate-based resin include ethylene-vinyl acetate copolymers and the like.
[0093] The saponification degree of the polyvinyl alcohol resin is preferably 70 mol% to 99.5 mol%, more preferably 95 mol% to 99.3 mol%. That is, the saponification degree is preferably 70 to 99.5 mol%, more preferably 95 to 99.3 mol%.
[0094] By using the above polyvinyl alcohol resin, the ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin and the viscosity can be adjusted to within predetermined ranges.
[0095] The polyvinyl alcohol resin may be used alone or in combination. By using the polyvinyl alcohol resins, the viscosity can be easily adjusted to a predetermined range, and a slurry composition for a ceramic green sheet having excellent viscosity stability over time can be prepared.
[0096] The acetalization is preferably carried out in an aqueous solvent, in a mixed solvent of water and an organic solvent compatible with water, or in an organic solvent.
[0097] As the organic solvent compatible with water, for example, an alcohol organic solvent can be used.
[0098] Examples of the organic solvent include alcohol organic solvents, aromatic organic solvents, aliphatic ester solvents, ketone solvents, lower alkane solvents, ether solvents, amide solvents, and amine solvents.
[0099] Examples of the alcohol-based organic solvent include methanol, ethanol, n-propanol, isopropanol, n-butanol, and tert-butanol.
[0100] Examples of the aromatic organic solvent include xylene, toluene, ethylbenzene, and methyl benzoate.
[0101] Examples of the aliphatic ester solvent include methyl acetate, ethyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, methyl acetoacetate, and ethyl acetoacetate.
[0102] Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methylcyclohexanone, benzophenone, and acetophenone.
[0103] Examples of the lower alkane solvent include hexane, pentane, octane, cyclohexane, and decane.
[0104] Examples of the ether solvent include diethyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol diethyl ether.
[0105] Examples of the amide solvent include N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and acetanilide.
[0106] Examples of the amine solvent include ammonia, trimethylamine, triethylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, aniline, N-methylaniline, N,N-dimethylaniline, and pyridine.
[0107] These solvents may be used as a single component (Japanese: monomer) or as a mixture of two or more thereof. Among these solvents, ethanol, n-propanol, isopropanol, and tetrahydrofuran are particularly preferred from the viewpoint of solubility in the resin and ease of purification.
[0108] The above-mentioned acetalization is preferably carried out in the presence of an acid catalyst.
[0109] The acid catalyst is not particularly limited, and examples thereof include mineral acids such as sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, carboxylic acids such as formic acid, acetic acid, and propionic acid, and sulfonic acids such as methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid. These acid catalysts may be used alone or in combination of two or more compounds. Among them, hydrochloric acid, nitric acid, and sulfuric acid are preferred, and hydrochloric acid is particularly preferred.
[0110] As the aldehyde used in the acetalization, there can be mentioned aldehydes having a chain aliphatic group, a cyclic aliphatic group or an aromatic group having 1 to 10 carbon atoms. As these aldehydes, conventionally known aldehydes can be used. The aldehyde used in the acetalization reaction is not particularly limited, and examples thereof include aliphatic aldehydes, aromatic aldehydes, and the like.
[0111] Examples of the aliphatic aldehydes include formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, n-hexanal, 2-ethylbutyraldehyde, 2-ethylhexanal, n-heptylaldehyde, n-octanal, n-nonylaldehyde, n-decanal, and valeraldehyde.
[0112] Examples of the aromatic aldehyde include benzaldehyde, cinnamaldehyde, 2-methylbenzaldehyde, 3-methylbenzaldehyde, 4-methylbenzaldehyde, p-hydroxybenzaldehyde, m-hydroxybenzaldehyde, phenylacetaldehyde, and β-phenylpropionaldehyde.
[0113] These aldehydes may be used alone or in combination of two or more. As aldehydes, formaldehyde, acetaldehyde, butyraldehyde, 2-ethylhexanal, and n-nonanal are preferred, which have excellent acetalization reactivity, can provide sufficient internal plasticization effect to the generated resin, and can give good flexibility as a result. In addition, formaldehyde, acetaldehyde, and butyraldehyde are more preferred from the perspective of obtaining an adhesive composition having particularly excellent impact resistance and adhesion to metals.
[0114] The amount of the aldehyde added can be appropriately set according to the acetal group amount of the target polyvinyl acetal resin. In particular, if it is preferably 55 mol% or more and 95 mol% or less, and more preferably 60 mol% or more and 90 mol% or less relative to 100 mol% of polyvinyl alcohol, the acetalization reaction is efficiently carried out and the unreacted aldehyde is easily removed, so it is preferred. That is, the amount of the aldehyde added is preferably 55 to 95 mol%, and more preferably 60 to 90 mol%.
[0115] The temperature when adding the aldehyde (aldehyde charging temperature) is preferably 0°C or higher, more preferably 10°C or higher, preferably 38°C or lower, more preferably 35°C or lower. That is, the aldehyde charging temperature is preferably 0 to 38°C, more preferably 10 to 35°C.
[0116] By setting the aldehyde charging temperature as described above, the ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin and the viscosity can be within a predetermined range.
[0117] The acetalization reaction is preferably carried out by raising the temperature at a predetermined temperature raising rate and then maintaining the temperature for a predetermined period of time.
[0118] The temperature increase time in the acetalization reaction is preferably 60 minutes to 500 minutes, more preferably 120 minutes to 400 minutes. That is, the temperature increase time is preferably 60 to 500 minutes, more preferably 120 to 400 minutes.
[0119] The temperature increase rate is preferably 0.01°C / min to 2°C / min, more preferably 0.1°C / min to 1°C / min. That is, the temperature increase rate is preferably 0.01 to 2.0°C / min, more preferably 0.1 to 1°C / min.
[0120] It should be noted that the time from the start of the acetalization reaction (addition of aldehyde) to the start of the temperature increase (temperature increase start time) is preferably 10 minutes to 100 minutes, more preferably 20 minutes to 80 minutes. That is, the temperature increase start time is preferably 10 to 100 minutes, more preferably 20 to 80 minutes.
[0121] By heating at the above-mentioned heating rate and heating start time, the ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin, the viscosity and the particle size can be within the predetermined ranges.
[0122] The retention time in the acetalization reaction is preferably 0.1 hours to 7 hours, more preferably 0.5 hours to 5 hours. That is, the retention time is preferably 0.1 to 7 hours, more preferably 0.5 to 5 hours. By setting the retention time as the above, the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups in the polyvinyl acetal resin and the viscosity can be within a predetermined range.
[0123] The holding temperature in the acetalization reaction is preferably 45° C. to 75° C., more preferably 50° C. to 72° C., and even more preferably 59° C. to 71° C. That is, the holding temperature is preferably 45 to 75° C., more preferably 50 to 72° C., and even more preferably 59 to 71° C. By setting the holding temperature to the above, the ratio of the peak integrated value of the triplet unit formed by the three sequences of the structural unit having a hydroxyl group in the polyvinyl acetal resin and the viscosity can be within a predetermined range.
[0124] It should be noted that the total time of the temperature increase time and the holding time in the acetalization reaction is preferably 4 hours to 15 hours, more preferably 4.5 hours to 12 hours. That is, the total time is preferably 4 to 15 hours, more preferably 4.5 to 12 hours.
[0125] The average reaction temperature in the acetalization reaction is preferably 41°C to 60°C, more preferably 45°C to 55°C. That is, the average reaction temperature is preferably 41 to 60°C, more preferably 45 to 55°C. By setting the average reaction temperature, the ratio of the peak integral value of the triad unit formed by the three sequences of the structural units having hydroxyl groups in the polyvinyl acetal resin and the viscosity can be within a predetermined range. It should be noted that the average reaction temperature is obtained by calculating "temperature × time" in each step of the acetalization reaction and dividing the total value by the total time.
[0126] A slurry composition for ceramic green sheets can be prepared by mixing an organic solvent and a ceramic powder with the polyvinyl acetal resin of the present invention.
[0127] The organic solvent is not particularly limited, and for example, any solvent that can dissolve the polyvinyl acetal resin is not particularly limited, and examples thereof include ketones such as acetone, methyl ethyl ketone, dipropyl ketone, and diisobutyl ketone. In addition, alcohols such as methanol, ethanol, isopropyl alcohol, and butanol, and aromatic hydrocarbons such as toluene and xylene can be mentioned. In addition, esters such as methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, butyl butyrate, methyl valerate, ethyl valerate, butyl valerate, methyl caproate, ethyl caproate, butyl caproate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate can be mentioned. In addition, methyl cellosolve, ethyl cellosolve, butyl cellosolve, terpineol, dihydroterpineol, butyl cellosolve acetate, butyl carbitol acetate, terpineol acetate, and dihydroterpineol acetate can be mentioned. In particular, alcohols, ketones, aromatic hydrocarbons, and mixed solvents thereof are particularly preferred from the viewpoint of coating properties and drying properties, and mixed solvents of ethanol and toluene and mixed solvents of methyl ethyl ketone and toluene are more preferred.
[0128] The content of the organic solvent in the slurry composition for ceramic green sheets is set according to the type of polyvinyl acetal resin used, etc., and is not particularly limited. If it is too little, it is difficult to exert the solubility required for mixing. In addition, if it is too much, the viscosity of the slurry composition for ceramic green sheets sometimes becomes too low, and the handling property when making ceramic green sheets deteriorates. Therefore, the content of the organic solvent is preferably 20% by weight or more and 80% by weight or less. That is, the content of the organic solvent is preferably 20 to 80% by weight.
[0129] As the above-mentioned ceramic powder, the metal or non-metal oxide or non-oxide powder used in the manufacture of ceramics can be cited. In addition, the composition of these powders can be a single composition, and the powder in the compound state can also be used alone or in combination. It should be noted that the constituent elements of the metal oxide or non-oxide, including cations or anions, can all be formed by a single element, can also be formed by multiple elements, and can also include additives added to improve the characteristics of the oxide or non-oxide. Specifically, oxides, carbides, nitrides, borides, sulfides, etc. of Li, K, Mg, B, Al, Si, Cu, Ca, Sr, Ba, Zn, Cd, Ga, In, Y, lanthanides, actinides, Ti, Zr, Hf, Bi, V, Nb, Ta, W, Mn, Fe, Co, Ni, etc. can be cited.
[0130] In addition, if specific substances of oxide powders containing multiple metal elements, which are generally called composite oxides, are classified according to their crystal structures, substances having a perovskite structure include: NaNbO 3 、SrZrO 3 、PbZrO 3 、SrTiO 3 、BaZrO 3 、PbTiO 3 、BaTiO 3 As the substance having a spinel structure, there are: MgAl 2 O 4 、ZnAl 2 O 4 、CoAl 2 O 4 、NiAl 2 O4、MgFe 2 O 4 As a substance having an ilmenite structure, MgTiO 3 、MnTiO 3 、FeTiO 3 As a substance having a garnet structure, GdGa 5 O 12 , Y 6 Fe 5 O 12 Among them, the modified polyvinyl acetal resin of the present invention is for BaTiO 3 The ceramic green sheet obtained by mixing the powders shows high properties.
[0131] The slurry composition for ceramic green sheets may contain a plasticizer. By adding a plasticizer, the mechanical strength and flexibility of the obtained ceramic green sheets can be greatly improved.
[0132] Examples of the plasticizer include phthalic acid diesters such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), adipic acid diesters such as dioctyl adipate, triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, triethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-2-ethylbutyrate, tetraethylene glycol-di-heptanoate, and alkylene glycol diesters such as triethylene glycol-di-heptanoate.
[0133] The average particle size of the ceramic powder is not particularly limited, but is preferably 0.5 μm or less for, for example, production of a thin-layer ceramic green sheet (thickness 5 μm or less).
[0134] In the slurry composition for ceramic green sheets, the preferred lower limit of the content of the plasticizer is 7 parts by weight, and the more preferred lower limit is 8.5 parts by weight, and the preferred upper limit is 40 parts by weight, and the more preferred upper limit is 30 parts by weight, relative to 100 parts by weight of the polyvinyl acetal resin. That is, the content of the plasticizer is preferably 7 to 40 parts by weight, and more preferably 8.5 to 30 parts by weight.
[0135] The ceramic green sheet slurry composition may contain other resins such as polyvinyl acetal resin, acrylic resin, ethyl cellulose, etc. other than the polyvinyl acetal resin of the present invention within a range that does not impair the effects of the present invention. In such a case, the content of the polyvinyl acetal resin of the present invention is preferably 50% by weight or more relative to the total binder resin.
[0136] The slurry composition for ceramic green sheets may contain dispersants, antioxidants, ultraviolet absorbers, surfactants, fillers, release agents, etc. as needed. Other resins such as acrylic resins and urethane resins may also be added in small amounts as needed.
[0137] The method for producing the slurry composition for ceramic green sheets is not particularly limited, and examples thereof include a method of mixing the polyvinyl acetal resin of the present invention, an organic solvent, ceramic powder, and various additives added as needed using various mixers such as a ball mill, a mixing mill, and a three-roll mill.
[0138] After the slurry composition for ceramic green sheets is applied, it is dried by heating to obtain ceramic green sheets.
[0139] The ceramic green sheets can be used to manufacture ceramic electronic components. For example, the ceramic electronic components can be manufactured by applying an electrode layer paste on the surface of the ceramic green sheets, and degreasing and firing the laminated body obtained by stacking and heat-pressing the ceramic green sheets with the electrode layers formed thereon.
[0140] The method for applying the slurry composition for ceramic green sheets is not particularly limited, and examples thereof include methods using a roll coater, a die coater, a curtain coater, etc. As other specific methods, conventionally known methods can be used.
[0141] The ceramic electronic components are not particularly limited, and examples thereof include laminated ceramic capacitors, laminated ceramic inductors, capacitors, piezoelectric actuators, laminated varistors, laminated thermistors, EMI filters, aluminum nitride multilayer substrates, aluminum oxide multilayer substrates, etc. Such laminated ceramic capacitors are also one of the present invention.
[0142] In the method for producing the ceramic electronic component, a step of applying an electrode layer paste on the surface of the ceramic green sheet is performed.
[0143] As the electrode layer paste, for example, polyvinyl acetal resin, ethyl cellulose, acrylic resin, etc. can be dissolved in an organic solvent as a binder resin, and a conductive powder can be dispersed. These resins can be used alone or in combination of two or more. The electrode layer paste containing polyvinyl acetal resin shows excellent adhesion to the ceramic green sheet in the heating and pressing process, so it is preferred.
[0144] In the manufacturing method of the above-mentioned ceramic electronic component, after the above-mentioned ceramic green sheets with electrode layers are produced, the ceramic green sheets with electrode layers produced in the same manner are stacked and heated and pressed to obtain a stacked body, which is then degreased and fired, thereby obtaining a stacked ceramic electronic component that solves problems such as sheet erosion (Japanese: シートアタック) and cracks.
[0145] It should be noted that the heat compression bonding step and the step of degreasing and firing the laminated body are not particularly limited, and conventionally known methods can be used.
[0146] Effects of the Invention
[0147] According to the present invention, a polyvinyl acetal resin can be provided, which, particularly when used as a binder for ceramic green sheets, can produce ceramic green sheets with excellent sheet corrosion resistance and tensile strength, and can produce laminated ceramic capacitors that are less likely to suffer from degradation of electrical characteristics and deterioration of defective rates and have excellent reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0148] Figure 1 The polyvinyl acetal resin obtained in Example 6 was 13 C-NMR measurement, measurement data when measuring the ratio of the peak integrated value of a triplet unit consisting of three sequences of structural units having a hydroxyl group. DETAILED DESCRIPTION
[0149] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0150] (Example 1)
[0151] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1750, degree of saponification 99.1 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 20°C, and 200 g of hydrochloric acid with a concentration of 35% by weight and 115 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 60 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.3°C / min (heating time 150 minutes), and the acetalization reaction was carried out at 65°C for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0152] (Example 2)
[0153] 3000 g of pure water was added to 193 g of polyvinyl alcohol resin (average degree of polymerization 1750, saponification degree 99.1 mol%, first PVA) and 17 g of polyvinyl alcohol resin (average degree of polymerization 800, saponification degree 98.4 mol%, second PVA), and the mixture was dissolved by stirring at 90°C for about 2 hours. The solution was cooled to 20°C, 200 g of hydrochloric acid with a concentration of 35% by weight and 120 g of n-butyraldehyde were added thereto, and after 60 minutes from the addition of n-butyraldehyde, the temperature was increased at a rate of 0.3°C / min (heating time 150 minutes), and the acetalization reaction was carried out by maintaining the temperature at 65°C for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of polyvinyl alcohol acetal resin.
[0154] (Example 3)
[0155] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 20° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 115 g of n-butyraldehyde were added thereto, and after 60 minutes from the addition of n-butyraldehyde, the temperature was increased at a rate of 0.30° C. / min (heating time 150 minutes), and the acetalization reaction was carried out at 65° C. for 2 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0156] (Example 4)
[0157] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 2500, degree of saponification 96.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 20°C, and 200 g of hydrochloric acid with a concentration of 35% by weight and 115 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.3°C / min (heating time 150 minutes), and the acetalization reaction was carried out at 65°C for 2 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0158] (Example 5)
[0159] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1000, degree of saponification 98.0 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 20° C., and 200 g of hydrochloric acid with a concentration of 35% by weight and 120 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.12° C. / min (heating time 390 minutes), and the acetalization reaction was carried out at 65° C. for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of the polyvinyl alcohol acetal resin.
[0160] (Example 6)
[0161] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 20° C., and 200 g of hydrochloric acid with a concentration of 35% by weight and 120 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.12° C. / min (heating time 390 minutes), and the acetalization reaction was carried out at 65° C. for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0162] (Example 7)
[0163] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 30°C, and 200 g of hydrochloric acid with a concentration of 35% by weight and 120 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.10°C / min (heating time 260 minutes), and the acetalization reaction was carried out at 55°C for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0164] (Example 8)
[0165] 3000 g of pure water was added to 147 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%, first PVA) and 63 g of polyvinyl alcohol resin (average degree of polymerization 800, degree of saponification 98.4 mol%, second PVA), and the mixture was dissolved by stirring at 90°C for about 2 hours. The solution was cooled to 30°C, 200 g of hydrochloric acid with a concentration of 35% by weight and 120 g of n-butyraldehyde were added thereto, and after 30 minutes from the addition of n-butyraldehyde, the temperature was increased at a rate of 0.10°C / min (heating time 260 minutes), and the acetalization reaction was carried out at 55°C for 3 hours, after which the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of polyvinyl alcohol acetal resin.
[0166] (Example 9)
[0167] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 20°C, and 200 g of hydrochloric acid with a concentration of 35% by weight and 115 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.20°C / min (heating time 150 minutes), and the acetalization reaction was carried out at 50°C for 5 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0168] (Example 10)
[0169] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 20°C, and 200 g of hydrochloric acid with a concentration of 35% by weight and 115 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.33°C / min (heating time 150 minutes), and the acetalization reaction was carried out at 70°C for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0170] (Example 11)
[0171] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 10°C, and 200 g of hydrochloric acid with a concentration of 35% by weight and 120 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.37°C / min (heating time 150 minutes), and the acetalization reaction was carried out at 65°C for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0172] (Example 12)
[0173] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 99.0 mol%), and the mixture was dissolved by stirring at 90° C. for about 2 hours. The solution was cooled to 20° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 115 g of n-butylaldehyde were added thereto, and after 60 minutes from the addition of n-butylaldehyde, the temperature was increased at a temperature increase rate of 0.30° C. / min (temperature increase time 150 minutes), and the acetalization reaction was carried out by maintaining the temperature at 65° C. for 1.5 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0174] (Comparative Example 1)
[0175] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 98.0 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butyraldehyde were added thereto, and 30 minutes after the addition of n-butyraldehyde, the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and the reaction was terminated. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0176] (Comparative Example 2)
[0177] 3100 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 3000, degree of saponification 98.5 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 160 g of n-butylaldehyde were added thereto, and 30 minutes after the addition of n-butylaldehyde, the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and the reaction was terminated. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0178] (Comparative Example 3)
[0179] 3100 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 800, degree of saponification 98.4 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 150 g of n-butylaldehyde were added thereto, and 30 minutes after the addition of n-butylaldehyde, the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and the reaction was terminated. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0180] (Comparative Example 4)
[0181] 3100 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 800, degree of saponification 98.4 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 20° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 145 g of n-butyraldehyde were added thereto, and 30 minutes after the addition of n-butyraldehyde, the temperature was increased at a rate of 0.25° C. / min (heating time 150 minutes), and the acetalization reaction was carried out at 58° C. for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0182] (Comparative Example 5)
[0183] 3000 g of pure water was added to 210 g of polyvinyl alcohol resin (average degree of polymerization 1700, degree of saponification 98.0 mol%), and the mixture was stirred at 90°C for about 2 hours to dissolve the mixture. The solution was cooled to 40°C, and 200 g of hydrochloric acid with a concentration of 35% by weight and 110 g of n-butylaldehyde were added thereto to precipitate the polyvinyl alcohol acetal resin. After 30 minutes from the addition of n-butylaldehyde, the temperature was increased at a rate of 0.17°C / min (heating time 30 minutes), and the acetalization reaction was carried out at 45°C for 3 hours, and then the reaction was terminated, and the mixture was neutralized, washed with water and dried by conventional methods to obtain a white powder of the polyvinyl alcohol acetal resin.
[0184] (Comparative Example 6)
[0185] 3000 g of pure water was added to 300 g of polyvinyl alcohol resin (average degree of polymerization 1800, degree of saponification 88.1 mol%), and the mixture was stirred at 90° C. for about 2 hours to dissolve the mixture. The solution was cooled to 40° C., 200 g of hydrochloric acid with a concentration of 35% by weight and 110 g of n-butylaldehyde were added thereto, and 30 minutes after the addition of n-butylaldehyde, the mixture was kept at 40° C. for 3 hours to carry out acetalization reaction, and the reaction was terminated. The mixture was neutralized, washed with water and dried by a conventional method to obtain a white powder of polyvinyl alcohol acetal resin.
[0186] (evaluate)
[0187] The polyvinyl acetal resins obtained in Examples and Comparative Examples were evaluated as follows.
[0188] (1) Evaluation of polyvinyl acetal resin
[0189] (1-1) Acetal group content, hydroxyl group content, acetyl group content
[0190] The obtained polyvinyl acetal resin was analyzed using an AV400 spectrometer (manufactured by Bruker). 1 The amount of acetal groups, the amount of hydroxyl groups and the amount of acetyl groups were calculated by H-NMR measurement.
[0191] The obtained polyvinyl acetal resin was dissolved in DMSO-D to a concentration of 1.6 wt %. 6 In the test solution. 1 H-NMR measurement was performed at 80°C.
[0192] (1-2) Ratio of the peak integrated value of the triplet unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin (ratio of the three-sequence hydroxyl structural unit)
[0193] The obtained polyvinyl acetal resin was analyzed using an AV400 spectrometer (manufactured by Bruker). 13 C-NMR measurement is performed to measure the ratio of the peak integrated value of the triad unit composed of three sequences of structural units having a hydroxyl group in the polyvinyl acetal resin. The details of the peak integrated value measurement are as described above.
[0194] The obtained polyvinyl acetal resin was dissolved in DMSO-D to a concentration of 12 wt%. 6 In the test solution. 13 C-NMR measurement was performed at 80°C.
[0195] It should be noted that the polyvinyl acetal resin obtained in Example 6 was subjected to 13 C-NMR measurement was performed to measure the ratio of the peak integral value of the triplet unit formed by the three sequences of the structural units having hydroxyl groups. The obtained measurement data are shown in Figure 1 .
[0196] (1-3) Average molecular weight determination
[0197] 0.04 g of the obtained polyvinyl acetal resin was added to 20 g of tetrahydrofuran, stirred and dissolved to prepare a resin solution. The resin solution was measured by gel permeation chromatography using LF-804 (manufactured by SHOKO) as a column to determine the weight average molecular weight (Mw) and number average molecular weight (Mn) based on polystyrene conversion. In addition, Mw / Mn was calculated based on the obtained Mw and Mn.
[0198] (1-4) Viscosity measurement
[0199] The obtained polyvinyl acetal resin was dissolved in an ethanol-toluene mixed solution at a weight ratio of 1:1 so as to be 5% by mass to prepare a sample for viscosity measurement. The viscosity of the obtained sample for viscosity measurement was measured using a B-type viscometer.
[0200] In addition, as a B-type viscometer, a TVB-10 type viscometer (manufactured by Toki Sangyo Co., Ltd.) was used, and the rotation speed and the rotor were set as follows for measurement.
[0201] Examples 1-3, 6-12, Comparative Examples 1, 5-6: Rotation speed 30 rpm, SPINDLE No. M1
[0202] Example 4, Comparative Example 2: Rotation speed 30 rpm, SPINDLE No. M2
[0203] Example 5, Comparative Examples 3 and 4: Rotation speed 60 rpm, SPINDLE No. M1
[0204] (2) Evaluation of polyvinyl acetal resin sheets
[0205] 10.0 parts by weight of the obtained polyvinyl acetal resin and 45 parts by weight of an ethanol / toluene mixed solvent (weight ratio 1:1) were added and stirred to dissolve, thereby obtaining a polyvinyl acetal resin composition.
[0206] The obtained polyvinyl acetal resin composition was applied onto a release-treated PET film using a coater so as to have a thickness of 20 μm after drying, and then heated and dried to produce a polyvinyl acetal resin sheet.
[0207] (2-1) Evaluation of sheet corrosion resistance
[0208] The obtained polyvinyl acetal resin sheet was cut into 1.5 cm x 10 cm squares and the weight was accurately measured. Then, the test piece was immersed in 10 ml of dihydroterpineol acetate at 23°C for 1 minute. Then, the test piece was taken out and dried at 150°C for 6 hours to completely dry the solvent.
[0209] After taking it out of the dryer, it was placed at room temperature for 1 hour and the weight was measured. The amount of resin dissolved was calculated based on the weight change before and after the test, and the dissolution rate was calculated based on the ratio of the dissolution amount to the weight of the test piece before the test, and evaluated according to the following criteria. It should be noted that the higher the dissolution rate value, the better the corrosion resistance of the sheet.
[0210] AA: Dissolution rate less than 2.0%
[0211] A: Dissolution rate is 2.0% or more and less than 2.5%
[0212] B: Dissolution rate is 2.5% or more and less than 3.0%
[0213] C: Dissolution rate is 3.0% or more
[0214] (3) Evaluation of Slurry Composition for Ceramic Green Sheet [Slurry Viscosity Stability over Time]
[0215] (Preparation of Inorganic Powder Dispersion)
[0216] 1 part by weight of polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd., BL-1) was added to a mixed solvent of 20 parts by weight of toluene and 20 parts by weight of ethanol, and the mixture was stirred and dissolved. Next, 100 parts by weight of barium titanate powder (manufactured by Sakai Chemical Industry Co., Ltd., BT01) was added to the resulting solution, and the mixture was stirred for 180 minutes using a bead mill (Readymill manufactured by IMEX Corporation), thereby preparing an inorganic powder dispersion.
[0217] (Preparation of resin solution)
[0218] 8 parts by weight of a polyvinyl acetal resin and 2.1 parts by weight of a plasticizer (G260 manufactured by Sekisui Chemical Co., Ltd.) were added to a mixed solvent of 45 parts by weight of ethanol and 45 parts by weight of toluene, and stirred and dissolved to prepare a resin solution.
[0219] (Preparation of slurry for ceramic green sheets)
[0220] The resin solution was added to the obtained inorganic powder dispersion, and the mixture was stirred for 90 minutes using a bead mill to obtain a slurry composition for ceramic green sheets.
[0221] (3-1) Slurry viscosity stability over time
[0222] The viscosity of the obtained slurry composition for ceramic green sheets was measured at 20°C and a rotation speed of 1.0 (1 / s) using a rheometer (Discovery HR 10 manufactured by TA Instruments). In addition, the viscosity of the slurry composition for ceramic green sheets after being placed at 23°C for one week was also measured under the same conditions, and the viscosity change rate before and after one week was calculated. The obtained viscosity change rate was evaluated according to the following criteria.
[0223] AA: Viscosity change rate is less than 400%
[0224] A: Viscosity change rate is more than 400% and less than 500%
[0225] B: Viscosity change rate is more than 500% and less than 600%
[0226] C: Viscosity change rate exceeds 600%
[0227] (4) Evaluation of ceramic green sheets
[0228] (Production of ceramic green sheets)
[0229] The obtained slurry was applied on a release-treated PET film using a coater so as to have a thickness of 20 μm after drying, and then heated and dried to produce a ceramic green sheet.
[0230] (4-1) Tensile strength
[0231] The obtained ceramic green sheets were subjected to fracture stress (MPa) measurement using a tensile tester (manufactured by Shimadzu Corporation, AUTOGRAPH AGS-J) at 23°C and a tensile speed of 20 mm / min in accordance with JIS K 7113. The fracture stress obtained was evaluated according to the following criteria.
[0232] AA: Breaking point stress exceeds 32MPa
[0233] A: The breaking point stress exceeds 30MPa and is below 32MPa
[0234] B: The breaking point stress exceeds 25MPa and is less than 30MPa
[0235] C: Breaking point stress is below 25MPa
[0236] [Table 1]
[0237]
[0238] Industrial Applicability
[0239] According to the present invention, a polyvinyl acetal resin can be provided, which, particularly when used as a binder for ceramic green sheets, can produce ceramic green sheets with excellent sheet corrosion resistance and tensile strength, and can produce laminated ceramic capacitors that are less likely to suffer from degradation of electrical characteristics and deterioration of defective rates and have excellent reliability.
Claims
1. A polyvinyl acetal resin, wherein the polyvinyl acetal resin is 13 The ratio of the peak integral value of the methine C atom represented by (a)' in the triple unit represented by the following formula (a) obtained by C-NMR measurement, i.e., nuclear magnetic resonance measurement, to the total peak integral values of the methine C atom represented by (a)', (b)', and (c)' in the triple unit represented by the following formula (a), the following formula (b), and the following formula (c) is 0.22 or more, The weight average molecular weight of the polyvinyl acetal resin is greater than 230,000. In the formula (b) and the formula (c), R is each independently hydrogen or a hydrocarbon group having 1 to 20 carbon atoms.
2. The polyvinyl acetal resin according to claim 1, wherein the polyvinyl acetal resin is 13 The ratio of the peak integral value of the secondary methyl C atom represented by (a)' in the triple unit represented by the formula (a) obtained by C-NMR measurement, i.e., nuclear magnetic resonance measurement, to the total peak integral values of the secondary methyl C atoms represented by (a)', (b)', and (c)' in the triple units represented by the formulas (a), (b), and (c) is greater than 0.
23.
3. The polyvinyl acetal resin according to claim 1 or 2, wherein the solution viscosity is 30 mPa·s or more and 600 mPa·s or less when a 5 mass % solution of the polyvinyl acetal resin dissolved in a 1:1 mixed solvent of ethanol and toluene is measured using a B-type viscometer at a solution temperature of 20°C. The polyvinyl acetal resin according to any one of claims 1 to 3, wherein the amount of hydroxyl groups is 23 mol% or more and 40 mol% or less. The polyvinyl acetal resin according to any one of claims 1 to 4, wherein the amount of acetyl groups is 0.1 mol% to 5 mol%. The polyvinyl acetal resin according to any one of claims 1 to 5, which has a molecular weight distribution of 2.75 or less. 7 . The polyvinyl acetal resin according to claim 1 , which is used for a ceramic green sheet. 8 . A slurry composition for ceramic green sheets, comprising the polyvinyl acetal resin according to claim 1 , an organic solvent, and a ceramic powder. 9 . A ceramic green sheet obtained by using the slurry composition for ceramic green sheets according to claim 8 . 10 . A multilayer ceramic capacitor obtained by using the ceramic green sheet according to claim 9 .
